Ultra-trace urinary clostebol findings: should delayed transfer from contaminated objects be considered? - Alberto Salomone; Pascal Kintz (Clinical Chemistry and Laboratory Medicine (CCLM), 2026)
Abstract Clostebol is an anabolic androgenic steroid prohibited at all times (class S1.1) by the World Anti-Doping Agency. In several countries, however, clostebol acetate is available without prescription in topical medicinal products, particularly Trofodermin ® , creating a substantial risk of inadvertent exposure. Experimental studies and case reports have demonstrated that indirect contact with a person or animal treated with clostebol acetate may result in detectable urinary concentrations of its main metabolite, 4-chloro-androst-4-en-3α-ol-17-one (M1). Such findings are frequently in the low or sub-ng/mL range. An insufficiently investigated mechanism is delayed exposure through objects, textiles, equipment, or environmental surfaces contaminated during an earlier use of Trofodermin ® . In this scenario, the interval of weeks or months would not represent persistence of clostebol in the athlete’s body. Rather, the prohibited substance would remain outside the body as a surface residue and would enter the athlete only after later contact with the contaminated object. Several real-world cases involving urinary M1 concentrations of approximately 20–500 pg/mL appear compatible with this mechanism after alternative sources have been investigated. Nevertheless, controlled clostebol-specific studies on aged environmental residues are currently lacking. The analytical sensitivity of modern anti-doping laboratories therefore requires a corresponding development in the scientific investigation of environmental transfer. Ultra-trace clostebol findings should prompt a structured assessment of contaminated objects and delayed secondary transfer, rather than an automatic assumption that the original use of Trofodermin ® must have occurred immediately before sample collection.